IMPLEMENTASI PENGGUNAAN ALAT LATIHAN KELINCAHAN PADA NOMOR KUMITE CABANG OLAHRAGA BELADIRI KARATE - Sri Nurhayati; Azhar Ramadhana Sonjaya; Asep Angga Permadi (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The..purpose of..this..study is to see the implementation of the..use of..agility training tools and..to find..out the results..of the..athlete's ability to..perform kumite. This implicit implements the experimental rules using the research design..One-grup..pretest-posttes. Subject...this study consisted of DOJO SMP PLUS NUURUL MUTTAQIIN karate athlete.. and the..sample used..in this..study was..14 people. The..kumite test is used..as..an instrument..for this..study. The..data review system used..is the..t test.. (paired..sampl.. t-test). The..results of..this research..prove thattcount for the kumite test as much as 21,002 while for ttable of 2.160. Therefore,tcount >  ttable and a calculated significance..of.. 0.000.<0.05. Therefore, the hypothesis..is..accepted. Based on the results of data processing and analysis using SPSS, it..can be..concluded that..the effective implementation..of the use of agility..training tools can increase the..agility of..athletes in performing kumite.